2013
DOI: 10.1016/j.bjan.2012.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Sedação Controlada pelo Paciente em Cirurgia Ortopédica sob Anestesia Regional: uma Nova Abordagem em Sedação

Abstract: This study suggests that patient-controlled sedation with propofol can be used efficiently in orthopedic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…This compares to 41 (2.3, 94.3) mg/hr in the current study, where the sedation was patient controlled. Ekin et al [14] equally reported lower doses of self-administered propofol in their study compared to our pilot study. As a whole, this suggests that the lower sedation doses in the IVR group seen in the pilot study was not the result of IVR, but a lower overall sedation requirement than what was administered as a routine by the anesthesiologist.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…This compares to 41 (2.3, 94.3) mg/hr in the current study, where the sedation was patient controlled. Ekin et al [14] equally reported lower doses of self-administered propofol in their study compared to our pilot study. As a whole, this suggests that the lower sedation doses in the IVR group seen in the pilot study was not the result of IVR, but a lower overall sedation requirement than what was administered as a routine by the anesthesiologist.…”
Section: Discussionsupporting
confidence: 43%
“…Each press of the PCS supplied a propofol bolus of 400mcg/kg Ideal Body Weight with a 5-minute lockout period. To prevent unwanted hypotension documented in previous studies [14] and on the advice from anesthesiologists reviewing the study protocol, an upper limit of 30mg per bolus was put in place as an additional safeguard. Anesthesiologists were advised that PCS should be the primary form of sedation but were not limited in giving additional sedation or analgesia if required in their clinical judgement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower-limb orthopedic surgery is frequently performed with regional anesthesia (23). Despite several advantages, those surgeries are associated with discomfort and worry for the patients.…”
Section: Discussionmentioning
confidence: 99%